Confiance numérique - Vincent Véchambre (Communication, 2014)
The author investigates the mechanisms that allow trust to build during exchanges between couchsurfers. A quantitative survey was conducted using feedback from 170 French members of the virtual community Couchsurfing.org. The author examines the way the fundamental and derivative processes of trust are mobilized by the couchsurfers in a context of anomy. Normative autonomy and the logic behind affinitive togetherness appear to be the main processes for establishing trusting relationships between couchsurfers.